Therapeutic Effectiveness and Safety of Repurposing Drugs for the Treatment of COVID-19: Position Standing in 2021 - Alam, Safaet; Kamal, Taslima Binte; Sarker, Md. Moklesur Rahman; Zhou, Jin-Rong; Rahman, S. M. Abdur; Mohamed, Isa Naina (Frontiers in Pharmacology, 2021)
COVID-19, transmitted by SARS-CoV-2 is one of the most hyped pandemic situations in the history of mankind which has already infected a huge population across the globe. This horrendously contagious viral outbreak was first identified in China and within a very short time it affected the world's health sector, transport, economic and academic backbone. In spite of the recent approval of few anti-COVID-19 vaccines, their unavailability and insufficiency along with lack of other potential therapeutic options are continuing to worsen the situation while many valuable lives are already lost. In this situation, researchers across the globe are focusing on repurposing prospective drugs and prophylaxis such as, favipiravir, remdesivir, chloroquine, hydroxychloroquine, ivermectin, lopinavir- ritonavir, azithromycin, doxycycline, ACEIs/ARBs, rivaroxaban, protease inhibitors etc. which were preliminarily based on in vitro and in vivo Pharmacological and Toxicological study reports followed by clinical applications. Based on available preliminary data derived from limited clinical trials, US National Institute of Health (NIH) and USFDA also recommended few drugs to be repurposed i.e. hydroxychloroquine, remdesivir and favipiravir. But later on, WHO recommended against the use of chloroquine, hydroxychloroquine, remdesivir, lopinavir/ritonavir in the treatment of COVID-19 infections. Combining basic knowledge of viral pathogenesis and pharmacodynamics of drug molecules as well as in silico approaches, many drug candidates have been investigated in clinical trials, some of which are proven to be partially effective against COVID-19 and some are not, and many of the other drugs are currently under extensive screening. The repurposing of prospective drug candidates from different stages of evaluation can be a handy wellspring in COVID-19 management and treatment along with approved anti-COVID19 vaccines. This review article combined the information from completed clinical trials, case series, cohort studies, meta-analysis and retrospective studies to focus on the current status of the repurposing drugs in 2021.